Blueprint : Shine Enterpise “3 Tier Nozzle Rack” / Nurul Farahain Junaidi - Junaidi, Nurul Farahain (2020)
Our company produces and sold favourable and beneficial products for storage product in bakery field. 3 Tier Nozzle Rack is a new product that being introduced in our company. This product is specifically for piping nozzle storage only. It only suitable for keeping the piping nozzle in smart way where the design of the piping nozzle is being displayed. Besides that, it is good to improve the space utilization of the company that sells thousands of piping nozzles. 3 Tier Nozzle Rack gives benefits to those who are dealing with the storage problem of the piping nozzles. The current storage drawer used by most of the company is impractical. Hence, we are here to introduced our product that can solve their problems